Antitumor activity and immunogenicity of recombinant vaccinia virus expressing HPV 16 E7 protein SigE7LAMP is enhanced by high-level coexpression of IGFBP-3 - Musil, Jan; Kutinova, L; Zurkova, K; Hainz, P; Babiarová, Katarína; Krystofova, J; Nemeckova, S (Cancer gene therapy, 2014)
We constructed recombinant vaccinia viruses (VACVs) coexpressing the insulin-like growth factor-binding protein-3 (IGFBP-3) gene and the fusion gene encoding the SigE7Lamp antigen. The expression of the IGFBP-3 transgene was regulated either by the early H5 promoter or by the synthetic early/late (E/L) promoter. We have shown that IGFBP-3 expression regulated by the H5 promoter yielded higher amount of IGFBP-3 protein when compared with the E/L promoter. The immunization with P13-SigE7Lamp-H5-IGFBP-3 virus was more effective in inhibiting the growth of TC-1 tumors in mice and elicited higher T-cell response against VACV-encoded antigen than the P13-SigE7Lamp-TK(-) control virus. We found that high-level production of IGFBP-3 enhanced virus replication both in vitro and in vivo, resulting in more profound antigen stimulation. Production of IGFBP-3 was associated with a higher adsorption rate of P13-SigE7Lamp-H5-IGFBP-3 to CV-1 cells when compared with P13-SigE7Lamp-TK(-). Intracellular mature virions (IMVs) of the IGFBP-3-expressing virus P13-SigE7Lamp-H5-IGFBP-3 have two structural differences: they incorporate the IGFBP-3 protein and they have elevated phosphatidylserine (PS) exposure on outer membrane that could result in increased uptake of IMVs by macropinocytosis. The IMV PS content was measured by flow cytometry using microbeads covered with immobilized purified VACV virions.
Keywords: lidský papilomavirus 16; Antibody Formation; Vaccinia virus; Female; vakcinace; Vaccination; Promoter Regions, Genetic; Viral Vaccines; replikace viru; Papillomavirus E7 Proteins; myši; Immunization; Mice; Insulin-Like Growth Factor Binding Protein 3; tvorba protilátek; T-lymfocyty; Papillomavirus E7 - proteiny; T-Lymphocytes; zvířata; Mice, Inbred C57BL; ženské pohlaví; virové vakcíny; Human papillomavirus 16; Animals; Antigens, Viral; IGFBP-3; antigeny virové; promotorové oblasti (genetika); Virus Replication; virus vakcinie; imunizace; myši inbrední C57BL